8‐1: Invited Paper: The Avegant Glyph: Optical Design Considerations and Approach to Near‐eye Display. Issue 1 (May 2016) - Dewald, D. Scott; Evans, Allan T.; Welch, Neil; Gross, Andrew; Hill, Geoff
Abstract : The Avegant Glyph tm is a new near‐eye product designed for mobile media consumption. It combines audio, a 3D capable display, head tracking, and other features into a novel product designed to mimic the movie theater experience. This paper will describe the evolution of the optical microdisplay system from early models to the final product, including novel illumination and projection optics that allow two complete projection engines to fit within the headband of the Glyph.